Growth behavior prediction of fresh catfish fillet with Pseudomonas aeruginosa under stresses of allyl isothiocyanate, temperature and modified atmosphere. (January 2015) - Pang, Yu-Hsin; Zhang, Li; Zhou, Siyuan; Yam, Kit L.; Liu, Linshu; Sheen, Shiowshuh
Abstract: Pseudomonas aeruginosa, an opportunistic pathogen which can be found on fresh catfish fillet, grows rapidly when temperature rises above 4 °C. The combination of allyl isothiocyanate (AIT) and modified atmosphere (MA) was applied and proved effective to retard the growth of P. aeruginosa . The objective of this research was to develop simple mathematical models to predict the growth behavior of P. aeruginosa in catfish fillet and its potential storage time (in abuse temperature condition) as a function of AIT and temperature with/without MA treatment. The antimicrobial effect of gaseous AIT (0, 18 and 36 μL/L) on the growth of P. aeruginosa cocktail was evaluated at 8, 15 and 20 °C. Furthermore, the effects of MA (49% CO2, 50.5% N2 and 0.5% O2 ) alone and AIT/MA combination were also investigated. These data obtained through an experimental design were used for model development. The regression models for lag phase, growth rate and "shelf life" (based on P. aeruginosa which closely related to Pseudomonas fluorescens and Pseudomonas pudita and all belong to the same RNA group used to classify the Pseudomonas at the subgenus level) were validated experimentally. Surface plot of models was also drawn to lucidly represent the interaction of AIT and temperature. The developed models may provide useful information for food industry in designing or selecting the proper packaging system with incorporation of AIT to attain the food safety with acceptable "shelf life" of fresh fish products under specified and potential abuse (with temperature deviation) distribution and storage conditions. Highlights: Pseudomonas aeruginosa showed faster growth potential in catfish fillet than liquid broth. "Shelf life" (lag phase basis) of fillet may be much extended using AIT and MA. Surface plots provide AIT/temperature interaction for "shelf life" optimization. Validated models may predict product life time to include abuse temperatures.